Environmental factors and gut microbiota: Toward better conservation of deer species - Wang, Yu; Xu, Bo; Chen, Huan; Yang, Fang; Huang, Jinlin; Jiao, Xin’an; Zhang, Yunzeng (Frontiers in Microbiology, 2023)
Thousands of microbial species inhabiting the animal gut, collectively known as the gut microbiota, play many specific functions in host nutrient metabolism and absorption, immune regulation, and protection from pathogenic bacteria. The gut microbiota composition is affected by several internal and external factors, such as the host genotype, dietary intake, breeding environment, and antibiotic exposure. As deer species are important members for maintaining ecosystem balance, understanding the effects of multiple factors on the gut microbiota of deer species, particularly endangered ones, is crucial. In this review, we summarize and discuss the factors that significantly affect the gut microbiota of deer and present the impacts of these factors on microbial composition. In particular, we focused on the changes in gut microbiota due to dietary differences under different conditions, including seasonal changes, different geographical locations, and captivity, as well as weaning and pathogen disturbance. Understanding the correlations between the gut microbiota composition and its driving factors is important for evaluating and improving the captive breeding environment for better conservation of endangered deer species, and reintroducing wild deer populations in the future.